A comparative assessment on performance, combustion and emission characteristics of diesel engine fuelled by juliflora biodiesel-diesel blends. Issue 1 (1st January 2023) - Rajendran, Silambarasan; Ganesan, Pranesh; Anandkumar, G
ABSTRACT: The present work aims at to explore the possibility of juliflora biodiesel as alternative fuel in a single cylinder, water cooled constant speed, direct injection diesel engine. The Performance parameters such as brake specific fuel consumption (BSFC), brake thermal efficiency (BTE) and exhaust gas temperature (EGT) are computed. The emission constituent's namely hydro carbon emission (HC), carbon monoxide emission (CO), smoke and oxides of nitrogen (NOx) are evaluated. It is found from the experimental investigation that JF20 shows that slight increase of BSFC, BTE and EGT which is closer to that of diesel fuel. Further, the HC, CO, smoke of JF20 is decreased when compared to that of diesel but the expense of NOx . Hence, JF20 can be selected as optimum blend which can be used in diesel engine without any major modification.